Interrogating the Narrative of New Masculinity in the Media: Remediation of Gender Dichotomy in the ABC Soy Sauce Comercial "Suami Sejati Mau Masak, Terima Kasih Kecap ABC” - Rara Mustika Ningrum (INFOKUM, 2025)
Advertisements play a significant role in shaping gender representation through the construction of signs and visual meanings. This study is motivated by the phenomenon of shifting gender roles in the domestic sphere, as represented in the ABC Soy Sauce advertisement “Suami Sejati Mau Masak, Terima Kasih Kecap ABC” (“A Real Husband Cooks, Thanks to ABC Soy Sauce”). The research aims to analyze how the advertisement constructs, negotiates, and deconstructs the meanings of masculinity and femininity. A qualitative descriptive method is applied using Jacques Derrida’s deconstruction. The data consist of dialogues, audio narration, and visual representations of characters in the advertisement. The findings reveal that the advertisement portrays the image of a modern man who is willing to cook as an effort to challenge traditional gender dichotomies. However, it simultaneously reproduces subtle patriarchal values. Women remain positioned at the center of domestic labor through the narrative of “helping” and specific visual symbols, while gender equality is commodified through the product’s role as a mediator. The study concludes that the advertisement offers only a pseudo-deconstruction: it appears progressive on the surface but ideologically maintains patriarchal myths within the domestic sphere.